End-Stage Renal Disease Status and Critical Illness in the Elderly - Sood, Manish M. (American Society of Nephrology, 2011)
BACKGROUND AND OBJECTIVES: Elderly patients (>65 years old) are a rapidly growing demographic in the ESRD and intensive care unit (ICU) populations, yet the effect of ESRD status on critical illness in elderly patients remains unknown. Reliable estimates of prognosis would help to inform care and management of this frail and vulnerable population. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The effect of ESRD status on survival and readmission rates was examined in a retrospective cohort of 14,650 elderly patients (>65 years old) admitted to 11 ICUs in Winnipeg, Manitoba, Canada between 2000 and 2006. Logistic regression models were used to adjust odds of mortality and readmission to ICU for baseline case mix and illness severity. RESULTS: Elderly ESRD patients had twofold higher crude in-hospital mortality (22% versus 13%, P < 0.0001) and readmission rate (6.4 versus 2.7%, P = 0.001). After adjustment for illness severity alone or illness severity and case mix, the odds ratio for mortality decreased to 0.85 (95% CI: 0.57 to 1.25) and 0.82 (95% CI: 0.55 to 1.23), respectively. In contrast, ESRD status remained significantly associated with readmission to ICU after adjustment for other risk factors (OR 2.06 [95% CI: 1.32, 3.22]). CONCLUSIONS: Illness severity on admission, rather than ESRD status per se, appears to be the main driver of in-hospital mortality in elderly patients. However, ESRD status is an independent risk factor for early and late readmission, suggesting that this population might benefit from alternative strategies for ICU discharge.